Melatonin and serotonin: Mediators in the symphony of plant morphogenesis. Issue 2 (11th January 2018) - Erland, Lauren A. E.; Shukla, Mukund R.; Singh, Amritpal S.; Murch, Susan J.; Saxena, Praveen K.
Abstract: Melatonin and serotonin are important signaling and stress mitigating molecules that play important roles across growth and development in plants. Despite many well‐documented responses, a systematic investigation of the entire metabolic pathway (tryptophan, tryptamine, and N ‐acetylserotonin) does not exist, leaving many open questions. The objective of this study was to determine the responses of Hypericum perforatum (L.) to melatonin, serotonin, and their metabolic precursors. Two well‐characterized germplasm lines (#4 and 112) created by mutation and a haploid breeding program were compared to wild type to identify specific responses. Germplasm line 4 has lower regenerative and photosynthetic capacity than either wild type or line 112, and there are documented significant differences in the chemistry and physiology of lines 4 and 112. Supplementation of the culture media with tryptophan, tryptamine, N ‐acetylserotonin, serotonin, or melatonin partially reversed the regenerative recalcitrance and growth impairment of the germplasm lines. Quantification of phytohormones revealed crosstalk between the indoleamines and related phytohormones including cytokinin, salicylic acid, and abscisic acid. We hypothesize that melatonin and serotonin function in coordination with their metabolites in a cascade of phytochemical responses including multiple pathways and phytohormone networks to direct morphogenesis and protect photosynthesis in H. perforatum .